Association between Geriatric Nutrition Risk Index and depression in older hemodialysis patients with and without type 2 diabetes mellitus: a multicenter cross-sectional study - Zhang, Jinwen; Gao, Jing; Gaowa, Siqin; Han, Peipei; Chen, Xiaoyu; Cai, Pingping; Guo, Jiangling; Wu, Qianhao; Miao, Jingjie; Zhao, Chengzhang; Zhang, Keying; Kong, Lingyao; et al. (Frontiers in Endocrinology, 2025)
ObjectivesThe purpose of this study was to observe the relationship between the Geriatric nutrition risk index (GNRI) and depression in the presence or absence of type 2 diabetes mellitus (T2DM) in older adults undergoing hemodialysis.DesignIn this multicenter cross-sectional study, 684 clinically stable hemodialysis patients aged ≥60 years (431 men; mean age: 69.6 ± 6.6 years) were included from seven dialysis units in Shanghai, China. Measures: Depressive symptoms were assessed using the PHQ-9 scale, and T2DM diagnoses were determined by medical records. Multinomial logistic regression was performed to evaluate the association between Geriatric Nutritional Risk Index (GNRI) and depression.ResultsHemodialysis patients with diabetes had a high prevalence of depression (39.4%). In diabetes patients, GNRI was associated with depression after adjusting covariates [OR=0.984; 95% confidence interval (CI) = 0.969–0.999, P=0.046]. However, no significant association was found between GNRI and depression in the non-diabetes hemodialysis patients (P > 0.05).ConclusionsThis cross-sectional study examines the relationship between the GNRI and depression in hemodialysis patients with T2DM rather than the non-T2DM group. Further studies are needed to investigate more causal relationships between GNRI and depression in patients with T2DM.